TINDAK TUTUR ASERTIF GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA I TAMPAKSIRING BALI - widiasri, dewaayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2020)
The purpose of this study was to determine the use of assertive speech acts based on form and function in class X at SMA I Tampaksiring, Bali. The data collection method used was non-participant observation method and interview method with recording technique and note taking technique. The data analysis used qualitative methods with pragmatic matching techniques based on the context of the speech events of the learning process in the classroom. The results showed that there were four uses of assertive speech acts used by teachers and students of class X SMA I Tampaksiring, namely stating, informing, suggesting, and boasting. hese four types of speech acts function to improve students understanding of the learning material so that learning targets are achieved.